The changing tax risk-management landscape: Initial insights from the United States of America, the United Kingdom and South Africa - Segal, Talya (My University, 2014)
Tax risk-management is a topical issue which delves into the governance, control structures and risk-management plans, and policies of companies. The aim of this research is to explore the tax risk-management concept, specifically focusing on and analysing how perceptions of tax risk-management have changed. The research will centre on regulatory and control and risk-management corporate governance developments over the past decade, locally and internationally. An analysis will be performed on how these developments have resulted in changes in tax risk-management. The research will also examine, through analysis of the literature, what the main tax risks facing companies are and, in this context, whether or not there has been a change in tax risk- management. It is stated, however, that the research is exploratory in nature and does not purport to be a complete account of tax risk-management